Respuesta :
Answer:
S={( 1 )}
Step-by-step explanation:
-3x²+6x+1=4
-3x²+6x+1-4=0
-3x²+6x-3=0
∆=b²-4.a.c
∆=(6)²-4.(-3).(-3)
∆=36-36
∆=0
x'=x"=-b/2a=-(+6)/2.(-3)=-6/-6=1
Answer:
Discriminant = 0; 1 real root
Step-by-step explanation:
-3x²+6x+1=4 (subtract 4 from each side)
-3x²+6x+1 - 4 = 0
-3x²+6x-3 = 0 (factorize 3 out of the left side)
3(-x²+2x-1) = 0
-x²+2x-1 = 0
Recall that for a quadratic equation in the form:
Ax² + Bx + C = 0, the discriminant = B²-4AC
in our case, A = -1, B = 2, = -1
discriminant = B²-4AC
= 2² - 4 (-1)(-1)
= 4 - 4(1)
= 4 - 4
= 0
Recall that when discriminant = 0, the quadratic equation has 1 real root. (answer)